Yields And Quality Of Peas Varieties In Latvian Agroclimatic Conditions For Organic Farming (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Article summarizes results of study detecting the best varieties of peas cultivated in Latvian organic farming conditions. Study was conducted with new varieties of two species of crop peas: Pisum arvense L. (Pink flower varieties) – Retrija, Almara and Vitra, and Pisum sativa L. (White flower varieties) – Lasma and Zaiga. All varieties were selected in Latvia. The best among white flower varieties in terms of crop productivity was Zaiga variety, where yield was 1.45-1.48 t ha-1. Among pink flower varieties of peas, the most productive was Almara variety, with crop productivity of 1.36-1.69 t ha-1. Retrija variety of peas excels other studied varieties by total protein content and taste properties.